PERAN SEKRETARIS DAN DATA ANALYST DALAM STRATEGI BRANDING “COOL ENOUGH” UNTUK MENINGKATKAN BRAND AWARENESS DAN BRAND ASSOCIATION DI SMOOLY SEMARANG - Axellia Verda Qania; Yanuar Luqman (Interaksi Online, 2026)
The increasing trend of healthy lifestyles following the COVID-19 pandemic has created opportunities for the healthy beverage industry, including Smooly Juice, while intense competition requires effective branding strategies to enhance brand awareness and build positive brand associations. This study aims to increase Smooly’s brand awareness from 30.5% to 65% and brand association as a health-conscious brand from 4% to 30% through the implementation of the #CoolEnough campaign, a digital and activation-based campaign focused on promoting healthy lifestyles through Instagram and TikTok content as well as interactive engagement activities. In this program, the Secretary was responsible for administrative management, documentation, partnership coordination, and licensing processes, while the Data Analyst was responsible for campaign data processing, social media performance monitoring, and pre-test and post-test analysis. The research applied the AISAS (Attention, Interest, Search, Action, Share) model with data collection methods including pre-test and post-test surveys, social media analytics, and documentation. The results showed an increase in brand awareness to 69% and brand association to 42%, indicating that the #CoolEnough campaign successfully enhanced brand visibility and strengthened consumer perception of Smooly as a healthy beverage brand.